Dampak Model Pembelajaran Auditory, Intellektualy, Repatition (AIR) terhadap Minat Belajar Siswa - Reza Miftah Rizkiardi; . Bambang Subali, (Universitas Pancasakti Tegal, 2018)
The purpose of this research is to know the impact of learning model of Auditory, Intellectual, Repatition (AIR) on the interest of learning science subjects in class III SDN 02 Banjaran. The background of this study was conducted to see whether there is an impact and change of interest in students' learning science subjects in class III SDN 02 Banjaran when the teacher uses the model of learning Auditory, Intellektualy, Repatition (AIR). The type of this research is descriptive qualitative research. The research method used is survey method, the technique used is interview and observation. Result of research based on interview and observation to teacher and student showed the impact of change of interest in science subject matter of weather material and its influence to class III student of SDN 02 Banjaran when the teacher in learning using learning model of Auditory, Intellektualy, Repatition (AIR).